Median sternotomy versus minimally invasive thymectomy for early-stage thymoma: A systematic review and meta-analysis protocol - Tianci, Chai (Medicine (Baltimore), 2019)
BACKGROUND: The completeness of resection is an important prognostic factor for early resectable thymoma. Since its inception 2 decades ago, median sternotomy has been recognized as the gold standard method for the treatment of all types and stages of thyomas. Minimally invasive surgical techniques, including video-assisted and robot-assisted surgery, have been rapidly developed as an alternative to traditional open approach surgery. Compared with traditional open approach surgery, minimally invasive approach has better cosmetic effect, faster improvement of lung function, reduction of surgical trauma, length of stay, and complications. We believe that this is an appropriate time and there is a need for a systematic, comprehensive, and objective assessment of the 2 surgical modalities in order to provide reliable evidence for clinicians to determine the best treatment for patients with early resectable thymoma. METHODS: Pubmed (Medline), Web of Science, Embase, Cochrane Central Register of Controlled Trials, and Google Scholar will be searched for relevant randomized controlled trials (RCTs), quasi-RCTs, and Hi-Q (high quality) prospective cohort trials published or unpublished in any language before March 1, 2020. Subgroup analysis will be performed in tumor pathological stage and ethnicity. PROSPERO registration number: CRD42019133724. RESULTS: The results of this study will be published in a peer-reviewed journal. CONCLUSION: This study will be the first to assess the efficacy and safety of median sternotomy recognized as the gold standard method for the treatment of all types and stages of thyomas and minimally invasive thymectomy for patients with early-stage thymoma. This study will assess whether minimally invasive thoracoscopic and robotic assisted thymectomy can be used as an alternative to traditional median sternotomy for patients with early resectable thymoma and provide high-quality and reliable evidence for clinicians’ decision-making.